2022
DOI: 10.1177/00343552221077942
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Influence of Perceived Stress on Subjective Well-Being of Student Veterans With and Without Disabilities: The Protective Role of Positive Traits and Social Support

Abstract: The transition from the regimented environment of military service to a less structured college lifestyle can be stressful for student veterans with and without disabilities, which highlights the importance of exploring protective person-environmental contextual factors that can help student veterans with and without disabilities manage their stress effectively, leading to enhanced well-being. The purpose of this cross-sectional correlational design study was to examine the role of positive person-environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Student veterans may experience challenges (e.g., drug use problems) completing their postsecondary education degree, which may negatively affect their academic life and outcomes (Umucu, 2017, 2022; Umucu, Lee, et al, 2021; Umucu, Lee et al, 2022; Umucu, Lo, et al, 2022). Therefore, our study has several implications for improving the understanding and support for veteran college students with disabilities, particularly those with substance use problems.…”
Section: Discussionmentioning
confidence: 99%
“…Student veterans may experience challenges (e.g., drug use problems) completing their postsecondary education degree, which may negatively affect their academic life and outcomes (Umucu, 2017, 2022; Umucu, Lee, et al, 2021; Umucu, Lee et al, 2022; Umucu, Lo, et al, 2022). Therefore, our study has several implications for improving the understanding and support for veteran college students with disabilities, particularly those with substance use problems.…”
Section: Discussionmentioning
confidence: 99%
“…Veteran population experiences a multitude of sociocultural, psychosocial, and socioeconomic barriers that impact their health and well‐being (Umucu, Chan, Phillips et al., 2022; Umucu, Ghosh et al., 2022; Umucu, Grenawalt et al., 2019; Umucu, Lee et al., 2023; Umucu, Lo et al., 2022; Umucu, Moser, & Bezyak, 2020). The objective of this study is to investigate whether employed veterans exhibit greater emotional well‐being outcomes in comparison to unemployed veterans, utilizing three distinct veteran sample groups.…”
Section: Discussionmentioning
confidence: 99%
“…Mental illness is prevalent within the veteran community due to exposure to traumatic events during combat and deployment (Grenawalt et al., 2021; Umucu, Lee et al., 2023). Notably, a study demonstrated that depression (13.5%) ranks as the most common mental health condition, followed by posttraumatic stress disorder (PTSD; 9.3%), substance use disorder (SUD; 8.3%), anxiety disorder (4.8%), and severe mental illness (SMI; 3.7%) (Trivedi et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Emphasizing positive psychological traits to promote happiness in individuals with disabilities can further benefit rehabilitation research, clinical practice, and consumer experiences (Chou et al, 2013; Dunn & Dougherty, 2005). Therefore, rehabilitation researchers and practitioners have been advocating for a paradigm shift from examining deficits in disability to focusing on positive psychosocial factors, including happiness (Chou et al, 2013; Dunn & Dougherty, 2005; Dunn et al, 2009; Fortuna et al, 2020; Huck et al, 2022; Grenawalt et al, 2022; Lee, 2022; Lee, Rumrill, et al, 2022; Lee, Rumril, Tansey, 2022; Moser et al, 2020; Phillips et al, 2022; Sánchez et al, 2019; Umucu, Lee, Berwick, et al, 2022; Umucu, Reyes, Carrola, et al, 2021; Umucu, Tansey, et al, 2021; Umucu, Wu, et al, 2020).…”
mentioning
confidence: 99%